SnS Quantum Dot–CsPbBr3 Perovskite Bulk Heterojunction for Enhanced Photoelectrical Conversion Efficiency. Issue 11 (11th September 2020) - Wang, Lian; Fu, Lin; Yin, Longwei
Abstract : Inorganic cesium lead halide perovskite solar cells (PSCs) have attracted great attention due to their remarkable thermal and moisture stability. However, the low photoelectric conversion efficiency (PCE) of inorganic PSCs due to the high trap state density, high carrier recombination rate, and poor carrier transport kinetics impedes their industrial applications. Herein, a remarkable bulk heterojunction structure coupling SnS quantum dots (QDs) with CsPbBr3 is prepared for the first time via a facile spin‐coating process using a SnS‐QD‐dispersed toluene solution as an antisolvent. The introduction of SnS QDs provides extra crystallization sites and promotes the crystallization of perovskites along (100) and (200) faces. Meanwhile, the bulk heterojunction structure with matched energy structure can effectively reduce the trap state density of the perovskite film and improves the dynamic performance of carriers, suppressing the charge recombination rate and effectively boosting the PCE of solar cells. As a result, the optimal bulk heterojunction solar cell achieves a PCE of 8.01%, about 52% higher than that of the pristine solar cell. This work provides a low‐cost and facile strategy for preparing high‐performance bulk heterojunction PSCs and an effective method to boost the PCE by nontoxic QDs. Abstract : Herein, a bulk heterojunction structure hybridizing SnS QDs and CsPbBr3 is designed as an absorber layer for solar cells. The prominent SnS QD–CsPbBr3 structure improves the crystallinity of perovskite, enhances the charge transfer efficiency, and reduces the trap state density of the CsPbBr3 film, thereby further boosting the photoelectric performance of perovskite solar cells.